Hungary's Integration into European Union Markets : Production and Trade Restructuring - Kamiński, Bartłomiej 1944- (The World Bank, 1999)
o 16 percent in 1996. The rapid pace of Hungary's turnaround seems to reflect the emergence of second-generation firms, mostly foreign-owned. Foreign-owned firms tend to be more export-oriented. Hungary has been one of the more successful transition economies because its economy was receptive to foreign direct investment from the outset. Between 1990 and 1997, Hungary absorbed roughly half of all foreign capital invested in Central Europe. This paper - a product of Trade, Development Research Group - is part of a larger effort in the group to study regional integration. The author may be contacted at bkaminski@worldbank.org